STROKE PREVENTION AND IMPLEMENTATION OF BOBATH EXERCISE IN THE ELDERLY IN BIRINGKANAYA, MAKASSAR CITY - Suharto Suharto; Suriani Suriani (Yayasan Education and Social Center, 2023)
The high elderly population in Indonesia encourages the need for efforts to create healthy and independent elderly. One of the impacts of the high population of elderly people is a decrease in the musculoskeletal system, a decrease in fat free mass or an increase in fat mass, which causes a decrease in muscle strength. Physical activity and physical exercise in the elderly are the main strategies that can play a role in preventing and slowing down the decline in function caused by aging and prevent the elderly from getting a stroke. This Community Service activity aims to increase community knowledge and skills in preventing and using bobath exercises in the elderly. This activity was carried out in Berua Village, Biringkanaya District, Makassar City in June 2023 which was attended by the elderly community, health cadres, community leaders and students. Implementation of activities with the method of lectures, discussions, demonstrations and practice in the elderly and post stroke patients. Evaluation of the activity begins with a pre-test regarding the participants' knowledge and skills in stroke and after several demonstrations, a post-test is carried out. The results of the activity showed that all participants experienced increased knowledge and skills in preventing and implementing bobath in the elderly. The conclusion from this community service activity is that the participants' knowledge and skills have increased after being given education about the prevention and application of bobath in the elderly and stroke patients.